Fipronil poisoning presenting as seizures and rhabdomyolysis - an unusual presentation - B. R. C. M. Basnayake; S. Yathukulan; P. Mayurathan (Asian Journal of Internal Medicine)
poisoning effects in humans are limited. Most are gastrointestinal and neurological effects which are short lasting; about three days. We report a case of fipronil poisoning presenting with convulsions. It was complicated with rhabdomyolysis, pigment induced acute kidney injury and altered liver profile.